Glukomanan Source From Araceae Family in Alas Purwo National Park - Gustini Ekowati; Rodiyati Azrianingsih (Natural B, Journal of Health and Environmental Sciences, 2011)
Araceae is a family of monocotyledonous flowering plants, often rhizomatous or tuberous, which flowers are borne on a type of inflorescence called a spadix. This Family has more than 1000 species, over 70 species were found in Java and eight species were found in East Java. But still no report whether the family grow in National Park of Alas Purwo, East Java. Furthermore, we explored the Araceae family that grow in the National Park Alas Purwo. We found six species of Araceae in the National Park of Alas Purwo, there are Dieffenbachia sp., Amorphophalus variabilis, Amorphophallus campanulatus var. sylvestris, Colocasia gigantea, Alocasia sp., and Xanthosomasagittifolia. The highest levels of glucomanan (2.24%) was found in Dieffenbachia sp and the lowest (0.98%) was found Xanthosoma sagittifolia.